Enhancing cauliflower growth under cadmium stress: synergistic effects of Cd-tolerant Klebsiella strains and jasmonic acid foliar application - Shahid, Shumila; Dar, Abubakar; Hussain, Azhar; Khalid, Imran; Latif, Muhammad; Ahmad, Hafiz Tanvir; Mehmood, Tariq; Aloud, Saud S. (Frontiers in Microbiology, 2024)
The pollution of heavy metals (HMs) is a major environmental concern for agricultural farming communities due to water scarcity which compels the farmers to use wastewater for irrigation purposes in Pakistan. Vegetables grown around the cities are irrigated with domestic and industrial wastewater having areas near mining, paint, and ceramic industries that pollute edible parts of crops with various HMs. Cadmium (Cd) is an extremely toxic metal in arable soil that enters the food chain and damages the native biota ultimately causing a reduction in plant growth and development. However, the use of microbes and growth regulator enhances plant growth and development as well as HMs immobilization into the cell wall and hinders their entry into the food chain. So, the integrated use of bacterial consortium along with exogenously applied jasmonic acid (JA) mitigates the adverse effect of metal stress ultimately reducing the metal mobility into roots by soil. Therefore, the current study was conducted to check the impact of Cd-tolerant bacteria and JA on the growth, nutrients status, and uptake of Cd in the cauliflower (Brassica oleracea) . Our results demonstrated that increasing concentration of Cd negatively affect growth, physiological, and biochemical attributes while use of bacterial consortium (SS7+SS8) with JA (40 μmol L-1) significantly improved chlorophyll contents, stem fresh and dry biomass (19.7%, 12.7%, and 17.3%), root length, and fresh and dry weights of root (28.8%, 15.2%, and 23.0%) and curd fresh and dry weights and diameter (18.7, 12.6, and 15.1%). However, the maximum reduction in soilCd, roots, and curd uptake was observed by 8%, 11%, and 9.3%, respectively, under integrated treatment as compared to the control. Moreover, integrating bacterial consortium and JA improves superoxidase dismutase (SOD) (16.79%), peroxidase dismutase (POD) (26.96%), peroxidase (POX) (26.13%), and catalase (CAT) (26.86%). The plant nitrogen, phosphorus, and potassium contents were significantly increased in soil, roots, and curd up to 8%, 11%, and 9.3%, respectively. Hence, consortium of Klebsiella strains in combination with JA is a potential phytostabilizer and reduce the uptake of Cd from soil to roots to alleviate the adverse impact on cauliflower’s growth and productivity.